Ceramic-based diaphragm for new energy automobile lithium battery and preparation method of ceramic-based diaphragm
By adopting a double-layer ceramic coating structure and a polydopamine-like layer on the lithium battery separator, the problem of reduced battery stability caused by changes in electrolyte is solved, and the higher electrolyte absorption capacity and the performance improvement of lithium batteries are achieved, and the service life of the battery is extended.
Patent Information
- Application Number
- CN202510044321.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-11
- Publication Date
- 2025-03-28
AI Technical Summary
Changes in the electrolyte during the charging and discharging of existing lithium battery separators lead to a decrease in battery stability and affecting service life.
The two-layer ceramic coating structure is adopted. The pore size of the nanoceramic aerogel in the outer ceramic coating is less than 200nm, and the pore size of the nanoceramic aerogel in the inner ceramic coating is 500-1000nm, forming a gradient pore size structure, and a polydopamine-like layer is formed on the surface of the ceramic coating, containing cerium oxide particles.
It improves the absorption and retention ability of the electrolyte, enhances the output power, energy efficiency and cycle stability of the lithium battery, and extends the service life and safety of the battery.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion battery separators, and in particular to a ceramic-based separator for a lithium battery of a new energy vehicle and a preparation method thereof. Background Art
[0002] Lithium batteries contain four main parts, namely the positive electrode, the separator, the negative electrode and the electrolyte. As a key part of lithium batteries, the separator can prevent battery short circuits and provide channels for the flow of lithium ions. With the development of science and technology, safety and environmental protection are ranked first in the development of batteries; since the separator is directly related to electrochemical performance, high temperature resistance to prevent the danger of battery short circuits, pore size less than 1μm to prevent organic electrolyte leakage, good mechanical properties, affinity for organic electrolytes, chemical stability in highly corrosive electrolytes, and long-term stable charge and discharge state are important indicators for evaluating the quality of separators; polyolefin separators are widely used in the market, and they have good mechanical strength, electrochemical stability and long-term charge and discharge capabilities. However, there are also disadvantages such as low ionic conductivity, low melting point so that strong thermal shrinkage will occur at high temperatures, low electrolyte absorption rate due to its own hydrophobicity, low lithium ion migration number and fast capacity decay at high discharge density. Coating polyolefin separators is a conventional means to improve their thermal stability, and the coating of inorganic ceramic particles has become the first choice. Inorganic ceramic particles, such as boehmite, alumina, silica, titanium dioxide, etc., are selected as coating materials for polyolefin separators due to their excellent thermal stability and electrolyte wettability to improve the thermal stability of polyolefin separators. However, the coating of inorganic ceramic particles alone has limited effect on the performance improvement of polyolefin separators.
[0003] For example, the Chinese patent, application number CN202211187793.3, a ceramic-based diaphragm for a new energy vehicle lithium battery and a preparation method thereof, comprising a PE-based membrane, a ceramic coating formed by coating a ceramic slurry on the surface of the PE-based membrane, and a polydopamine-like layer grafted on the surface of the ceramic coating; the ceramic slurry comprises the following components in parts by weight: 40-60 parts of nano-ceramic aerogel, 5-10 parts of polyethylene-vinyl alcohol sulfonate lithium, 10-15 parts of polyvinylidene fluoride, 5-10 parts of poly(4-styrene sulfonic acid) lithium salt, 3-8 parts of polymer binder, and 35-45 parts of solvent. The ceramic-based diaphragm prepared by the invention has good electrolyte wetting properties, can absorb and retain a considerable amount of electrolyte, has high ionic conductivity, lithium ions are easily separated and lithium ions can pass through the diaphragm quickly, thereby optimizing the electrochemical properties of the battery, and the thermal shrinkage rate is ≤2%, which can effectively improve the safety of the lithium battery.
[0004] However, during the discharge and storage process, the concentration of the electrolyte changes, which in turn affects changes in parameters such as battery voltage, resulting in reduced battery stability and shortening its service life. Summary of the invention
[0005] The embodiments of the present application provide a ceramic-based diaphragm for a new energy vehicle lithium battery and a preparation method thereof, thereby solving the problem of reduced battery stability caused by changes in the electrolyte during battery charging and discharging in the prior art, and achieving an increase in the battery's service life.
[0006] An embodiment of the present application provides a ceramic-based diaphragm for a lithium battery of a new energy vehicle, comprising a PE-based film and a ceramic coating on the surface of the PE-based film, wherein the ceramic coating comprises an inner and outer layer, and a polydopamine layer is grafted between the two ceramic coating layers; the ceramic coating is made by coating with a ceramic coating, and the dopamine layer is composed of a dopamine derivative containing a double bond, specifically methacrylamide dopamine, and the PE-based film is a 25 μm microporous film.
[0007] Furthermore, the ceramic slurry comprises the following components: 40-60 parts of nano ceramic aerogel, 5-10 parts of polyethylene-vinyl alcohol sulfonate lithium, 10-15 parts of polyvinylidene fluoride, 5-10 parts of poly(4-styrene sulfonic acid) lithium salt, 3-8 parts of polymer binder, and 35-45 parts of solvent; the nano ceramic aerogel is ZrO 2 -SiO 2 Composite aerogel, and ZrO 2 -SiO 2 The composite aerogel contains rare earth oxides, specifically CeO 2 .
[0008] Furthermore, the polymer binder is polyvinyl alcohol, and the solvent includes water and DMAC in a mass ratio of 1:10.
[0009] Furthermore, the ZrO 2 -SiO 2 The preparation method of the composite aerogel is specifically as follows: Add zirconium oxynitrate to 10%-60% ethanol aqueous solution and stir evenly to obtain a zirconium source solution. Add TEOS to 10%-60% ethanol aqueous solution and stir evenly to obtain a silicon source solution. Mix the zirconium source solution and the silicon source solution evenly. Add CeO 2 , react in a 50-70°C water bath with stirring for 24-36 hours, then add formamide and continue stirring for 30-60 minutes to obtain a mixed sol, soak the mixed sol in ethanol at 40-50°C for aging for 3-6 days, during which time the ethanol is replaced every 12-24 hours, and finally dry it through supercritical drying and then ball mill.
[0010] Furthermore, the mass ratio of Ce, Si and Zr is 0.05:1:1.
[0011] Furthermore, the content of the solvent ethanol aqueous solution used in the preparation of the nano-ceramic aerogel contained in the outer ceramic coating and the inner ceramic coating is different.
[0012] Furthermore, the solvent of the zirconium source solution and the silicon source solution in the nano-ceramic aerogel in the outer ceramic coating is a 10-30% ethanol aqueous solution; the solvent of the zirconium source solution and the silicon source solution in the nano-ceramic aerogel in the inner ceramic coating is a 40-60% ethanol aqueous solution.
[0013] The preparation method of the ceramic-based diaphragm for the lithium battery of new energy vehicles is as follows: Nano-ceramic aerogel, polyethylene-vinyl alcohol lithium sulfonate, polyvinylidene fluoride, poly(4-styrene sulfonic acid) lithium salt, and polymer binder are added to a solvent and stirred evenly to obtain a ceramic slurry. The ceramic slurry is coated on the surface of a PE base film and cured to obtain a semi-finished product. A dopamine derivative containing a double bond is added to a TRIS-HCl buffer solution, stirred to dissolve, and the semi-finished product is immersed therein. After deoxygenation with nitrogen for 30-60 minutes, the semi-finished product is taken out after irradiation with ultraviolet light for 4-6 hours, and the ceramic slurry is coated again and cured, and then washed alternately with methanol and water and dried.
[0014] Furthermore, the polydopamine-like layer also contains cerium oxide, and the specific steps are: A dopamine derivative containing a double bond is added to a TRIS-HCl buffer solution containing cerium oxide, and after stirring and dissolving, the semi-finished product is immersed therein, deoxygenated with nitrogen for 30-60 minutes, and then irradiated with ultraviolet light for 4-6 hours before being taken out; wherein the volume content of cerium oxide is 1-5%.
[0015] Furthermore, it is characterized in that the cerium oxide particles are selected to be large particles of 100-200nm or small particles of 50-100nm; Different combinations of cerium oxide particles are used for the outer ceramic coating, the middle polydopamine-like layer and the inner ceramic coating.
[0016] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages: First, the two layers of ceramic coating increase the contact area between the diaphragm and the electrolyte, and at the same time, a microporous structure is formed between the two layers of coating, which further improves the absorption and retention capacity of the electrolyte; thereby increasing the electrolyte reserve of the lithium battery during operation and reducing the performance degradation caused by insufficient electrolyte; by enhancing the absorption and retention capacity of the electrolyte and improving the ion conductivity, the two layers of ceramic coating improve the output power, energy efficiency and cycle stability of the battery; the dopamine layer forms a continuous and complete film-forming coating layer on the surface of the ceramic coating through self-oxidation polymerization reaction, thereby improving the overall performance of the coating; Second, the pore size of the nano-ceramic aerogel in the outer ceramic layer is less than 200nm, and the pore size of the nano-ceramic aerogel in the inner ceramic layer is 500-1000nm, forming a gradient pore size structure. The small pore size of the outer layer can effectively prevent large particles or other substances from entering the interior of the diaphragm while maintaining good electrolyte wettability; the large pore size of the inner layer is conducive to the rapid absorption and storage of the electrolyte, as well as the rapid conduction of lithium ions. The gradient pore size structure enables the electrolyte to be used more effectively, reducing the waste of the electrolyte, thereby improving the energy density and cycle life of the battery; Third, the presence of cerium oxide particles increases the contact area and interfacial interaction between the polydopamine-like layer and the inner and outer ceramic coatings. Since cerium oxide has good chemical stability and high surface energy, it can form stronger chemical bonds or physical adsorption with the functional groups in the polydopamine-like layer and the components in the ceramic coating. The addition of cerium oxide particles enhances the adhesion between the polydopamine-like layer and the inner and outer ceramic coatings, reduces the risk of interlayer delamination, and improves the overall stability and durability of the diaphragm. Fourthly, different combinations can be selected according to the environmental or climatic differences in different regions. The large-size particles in the inner layer can provide better structural support and increase the mechanical strength of the diaphragm; the small-size particles can fill the gaps more tightly, improve the density of the diaphragm, have a large specific surface area, increase the contact area with the electrolyte, and facilitate the rapid conduction of ions; large-size particles increase mechanical strength, and small-size particles increase density. DETAILED DESCRIPTION
[0017] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.
[0018] Embodiment 1: The present application discloses a ceramic-based diaphragm for a lithium battery of a new energy vehicle, comprising a PE-based film and a ceramic coating on the surface of the PE-based film, wherein the ceramic coating comprises an inner and outer layer, and a polydopamine-like layer is grafted between the two ceramic coating layers; the ceramic coating is made by coating a ceramic coating, and the dopamine layer is composed of a dopamine derivative containing a double bond, specifically methacrylamide dopamine; the PE-based film is a 25 μm microporous film; The ceramic coating is applied on one or both sides of the PE base film; The ceramic slurry comprises the following components in parts by weight: 40-60 parts of nano ceramic aerogel, 5-10 parts of polyethylene-vinyl alcohol sulfonate lithium, 10-15 parts of polyvinylidene fluoride, 5-10 parts of poly (4-styrene sulfonic acid) lithium salt, 3-8 parts of polymer binder, and 35-45 parts of solvent; the nano ceramic aerogel is ZrO 2 -SiO 2 Composite aerogel, and ZrO 2 -SiO 2 The composite aerogel contains rare earth oxides, specifically CeO 2 ; Wherein, the polymer binder is polyvinyl alcohol; the solvent includes water and DMAC, and the mass ratio is 1:10; ZrO 2 -SiO 2 The preparation method of the composite aerogel is specifically as follows: Zirconium oxynitrate was added to 30% ethanol aqueous solution and stirred evenly to obtain a zirconium source solution. TEOS was added to 30% ethanol aqueous solution and stirred evenly to obtain a silicon source solution. The zirconium source solution and the silicon source solution were mixed evenly, and CeO 2 , react in a water bath at 50-70°C with stirring for 24-36h, then add formamide and continue stirring for 30-60min to obtain a mixed sol, soak the mixed sol in ethanol at 40-50°C for aging for 3-6d, replace ethanol every 12-24h during this period, and finally dry it through supercritical drying and then ball mill it; The mass ratio of Ce, Si and Zr is 0.05:1:1, CeO 2 The particle size is 50-100nm.
[0019] The preparation method of the ceramic-based diaphragm for the new energy vehicle lithium battery is specifically as follows: Add nano-ceramic aerogel, polyethylene-vinyl alcohol lithium sulfonate, polyvinylidene fluoride, poly(4-styrene sulfonic acid) lithium salt, and polymer binder into a solvent, stir evenly to obtain a ceramic slurry, apply the ceramic slurry to the surface of a PE base film, and solidify to obtain a semi-finished product, add a dopamine derivative containing a double bond into a TRIS-HCl buffer, stir to dissolve, immerse the semi-finished product therein, deoxygenate with nitrogen for 30-60 minutes, irradiate with ultraviolet light for 4-6 hours, take out, apply the ceramic slurry again, solidify, wash with methanol and water alternately, and then dry; Among them, the ultraviolet light irradiation intensity is ≥180mW / m, and the immersion temperature is ≥25°C.
[0020] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: The two layers of ceramic coating increase the contact area between the diaphragm and the electrolyte, and at the same time, a microporous structure is formed between the two layers of coating, which further improves the absorption and retention capacity of the electrolyte; thereby increasing the electrolyte reserve of the lithium battery during operation and reducing the performance degradation or other parameter changes caused by insufficient electrolyte or electrolyte charging and discharging; by enhancing the absorption and retention capacity of the electrolyte and improving the ion conductivity, the two layers of ceramic coating improve the output power, energy efficiency and cycle stability of the battery; the dopamine layer forms a continuous and complete film-forming coating layer on the surface of the ceramic coating through a self-oxidation polymerization reaction, thereby improving the overall performance of the coating and improving the corrosion resistance and wear resistance of the coating; The polydopamine-like layer as an intermediate layer can improve the absorption capacity of the separator to the electrolyte and enhance the interaction between the separator and the electrolyte; and the polydopamine-like layer contains rich functional groups, which can form good chemical bonds with the inner and outer ceramic coatings, thereby enhancing the adhesion between the layers, reducing interlayer peeling, and improving the overall stability and durability of the separator; The outer ceramic coating consolidates the overall structure of the diaphragm, provides an additional physical barrier, and enhances the mechanical strength and thermal stability of the diaphragm; The double-layer ceramic coating enables the diaphragm to absorb and retain more electrolyte, thereby improving the wettability of the electrolyte; the ion conductivity is further improved, and lithium ions can pass through the diaphragm more quickly, optimizing the electrochemical performance of the battery; The two layers of ceramic coating form more ion transmission channels, making the transmission of lithium ions in the diaphragm smoother; improving ion conductivity reduces the internal resistance of the battery, improves the output power and energy efficiency of the battery, and the two-layer ceramic coating structure disperses the heat generated during the operation of the battery. At the same time, the ceramic material itself has high thermal stability; the two layers of ceramic coating increase the thickness of the diaphragm and the interaction force between the coatings, thereby improving the mechanical strength of the diaphragm; The combination of the double-layer ceramic coating and the polydopamine-like layer enhances the mechanical strength of the separator, enabling it to withstand greater stress and deformation, and also prevents lithium dendrites from piercing the separator, thereby improving the durability of the separator and extending the service life and safety of the lithium battery. The ceramic-based diaphragm prepared in Example 1 of the present invention was used as a sample for grouping experiments, wherein the proportion of the ceramic slurry was specifically grouped as follows: Group 1, inner ceramic coating: 60 parts of nano-ceramic aerogel, 10 parts of polyethylene-vinyl alcohol sulfonate lithium, 15 parts of polyvinylidene fluoride, 10 parts of poly(4-styrene sulfonic acid) lithium salt, 8 parts of polymer binder, and 45 parts of solvent; Outer ceramic coating: 40 parts of nano-ceramic aerogel, 5 parts of polyethylene-vinyl alcohol sulfonate lithium, 10 parts of polyvinylidene fluoride, 5 parts of poly (4-styrene sulfonic acid) lithium salt, 3 parts of polymer binder, and 35 parts of solvent; Group 2, inner ceramic coating: 55 parts of nano-ceramic aerogel, 8 parts of polyethylene-vinyl alcohol sulfonate lithium, 13 parts of polyvinylidene fluoride, 8 parts of poly(4-styrene sulfonic acid) lithium salt, 6 parts of polymer binder, and 42 parts of solvent; Outer ceramic coating: 45 parts of nano-ceramic aerogel, 7 parts of polyethylene-vinyl alcohol sulfonate lithium, 12 parts of polyvinylidene fluoride, 7 parts of poly (4-styrene sulfonic acid) lithium salt, 4 parts of polymer binder, 38 parts of solvent; Group 3, inner ceramic coating: 40 parts of nano-ceramic aerogel, 5 parts of polyethylene-vinyl alcohol sulfonate lithium, 10 parts of polyvinylidene fluoride, 5 parts of poly(4-styrene sulfonic acid) lithium salt, 3 parts of polymer binder, and 35 parts of solvent; Outer ceramic coating: 60 parts of nano-ceramic aerogel, 10 parts of polyethylene-vinyl alcohol sulfonate lithium, 15 parts of polyvinylidene fluoride, 10 parts of poly (4-styrene sulfonic acid) lithium salt, 8 parts of polymer binder, 45 parts of solvent; Group 4, inner ceramic coating: 45 parts of nano-ceramic aerogel, 7 parts of polyethylene-vinyl alcohol lithium sulfonate, 12 parts of polyvinylidene fluoride, 7 parts of poly(4-styrene sulfonic acid) lithium salt, 4 parts of polymer binder, and 38 parts of solvent; Outer ceramic coating: 55 parts of nano-ceramic aerogel, 8 parts of polyethylene-vinyl alcohol sulfonate lithium, 13 parts of polyvinylidene fluoride, 8 parts of poly (4-styrene sulfonic acid) lithium salt, 6 parts of polymer binder, 42 parts of solvent; Group 5, inner ceramic coating: 50 parts of nano-ceramic aerogel, 8 parts of polyethylene-vinyl alcohol sulfonate lithium, 12 parts of polyvinylidene fluoride, 7 parts of poly(4-styrene sulfonic acid) lithium salt, 5 parts of polymer binder, and 40 parts of solvent; Single layer group, containing only a single layer of ceramic coating and a polydopamine-like layer, ceramic coating: 50 parts of nano-ceramic aerogel, 8 parts of polyethylene-vinyl alcohol sulfonate lithium, 12 parts of polyvinylidene fluoride, 7 parts of poly (4-styrene sulfonic acid) lithium salt, 5 parts of polymer binder, and 40 parts of solvent; Outer ceramic coating: 50 parts of nano-ceramic aerogel, 8 parts of polyethylene-vinyl alcohol sulfonate lithium, 12 parts of polyvinylidene fluoride, 7 parts of poly (4-styrene sulfonic acid) lithium salt, 5 parts of polymer binder, 40 parts of solvent; Contact angle test: Use the solid drop method and electrolyte as the test liquid to measure the contact angle. Drop a drop of electrolyte with a volume of about 5uL into the injector, move the needle downward, and when the electrolyte contacts the sample surface, the injector returns to its original position, record the moment when the electrolyte is adsorbed on the sample surface, and calculate the contact angle.
[0021] Electrolyte absorption rate test: After cutting the sample, put it in a 60℃ oven for 24h, then weigh it and record the weight W at this time. 0, immerse the sample in the electrolyte for 30 minutes, take out the sample, wipe the electrolyte on the surface with filter paper, and measure the weight W of the sample at this time 1 , and then calculate the electrolyte absorption rate, the calculation formula is: absorption rate (%) = 100 × (W 1 -W 0 ) / W 0 ; Ionic conductivity test: In a glove box filled with argon, the sample was sandwiched between two stainless steel electrodes to assemble into a liquid electrolyte CR2016 button battery. The battery was placed in an oven and left to stand for 30 minutes at different temperatures (25-120°C). The ionic conductivity was measured using AC impedance spectroscopy in the frequency range of 1.0 Hz to 106 Hz. Thermal shrinkage test: Cut the sample into a disc with a diameter of 17 mm, clamp the sample between two glass sheets, place it in an oven, heat it to 150°C, and keep it for 30 minutes; Cycle performance test: Test LiFePO according to GB / T 31484-2015 4 The cycle performance of lithium batteries was tested at a temperature of 45°C, a humidity of 40%, and normal pressure for 50 cycles, 100 cycles, and 150 cycles; The specific test results are shown in Table 1 below: Table 1 Embodiment 2: The above embodiment optimizes the chemical properties of the diaphragm through a multi-layer ceramic coating, and is further improved on the basis of embodiment 1 in order to differentiate the coating effect and optimize the diaphragm performance.
[0022] The solvent concentrations used in preparing the nano-ceramic aerogels contained in the outer ceramic coating and the inner ceramic coating are different, specifically: The solvent of the zirconium source solution and the silicon source solution in the nano-ceramic aerogel in the outer ceramic coating is a 10-30% ethanol aqueous solution; The solvent of the zirconium source solution and the silicon source solution in the nano-ceramic aerogel in the inner ceramic coating is a 40-60% ethanol aqueous solution; The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: The increase in ethanol concentration may change the solubility of the silicon source in the water-alcohol mixed solution. As the ethanol concentration increases, the solubility of the silicon source decreases, causing the diffusion rate of the silicon source molecules in the solution to slow down, thereby affecting its hydrolysis and polymerization process; when the polymerization rate decreases, the silicon source molecules have more time to arrange and polymerize in an orderly manner, resulting in a smaller pore size. Therefore, the pore size of the nano-ceramic aerogel in the outer ceramic layer is less than 200nm, and the pore size of the nano-ceramic aerogel in the inner ceramic layer is 500-1000nm, forming a gradient pore size structure. The small pore size of the outer layer can effectively prevent large particles or other substances from entering the interior of the diaphragm while maintaining good electrolyte wettability; the large pore size of the inner layer is conducive to the rapid absorption and storage of the electrolyte, as well as the rapid conduction of lithium ions. The gradient pore size structure enables the electrolyte to be used more effectively, reducing the waste of the electrolyte, thereby improving the energy density and cycle life of the battery; The gradient pore size structure enables the polydopamine layer to better bond with the ceramic coating surface during the formation process. The outer small-pore coating provides a more delicate and uniform surface, which is conducive to the uniform distribution of dopamine molecules on the coating surface and the self-oxidation polymerization reaction, thereby forming a continuous and complete film-forming coating layer. This close combination improves the overall performance of the coating, including corrosion resistance, wear resistance and adhesion between coatings. The inner large-pore coating acts as a "reservoir" for the electrolyte, which can absorb and store a large amount of electrolyte. When the battery is charged and discharged, the electrolyte will flow and conduct rapidly in the inner large-pore layer, while the polydopamine-like layer acts as an intermediate layer, which can enhance the interaction between the diaphragm and the electrolyte, and improve the wettability and ion conductivity of the electrolyte. This interaction is not only conducive to the rapid transmission of lithium ions, but also can reduce the loss of electrolyte in the diaphragm, thereby improving the energy density and cycle life of the battery; In addition, the gradient pore size structure also enhances the mechanical strength and thermal stability of the diaphragm. The outer small pore size coating can prevent large particles or impurities from entering the battery, reducing the risk of internal short circuits in the battery. At the same time, this structure also disperses the heat generated during the operation of the battery, improves the thermal stability of the battery, and provides better support and protection for the polydopamine-like layer, enabling it to better play its role in the diaphragm. The outer layer of small-pore coating can control the penetration rate of the electrolyte, preventing the electrolyte from penetrating into the battery too quickly, thereby maintaining the uniform distribution of the electrolyte inside the battery. The inner layer of large-pore coating acts as a "reservoir" for the electrolyte, providing a stable supply of electrolyte during the battery charging and discharging process. The outer layer of small-pore coating maintains the stability of the electrolyte inside the battery and reduces the impact of electrolyte fluctuations on battery performance. The inner layer of large-pore coating increases the transmission speed of lithium ions, thereby improving the output power and energy efficiency of the battery. The large pore size of the inner layer provides more transmission channels for lithium ions, reduces the resistance of ion transmission, and improves ion conductivity. The small pore size of the outer layer plays a certain screening role, ensuring that only small molecules such as lithium ions can pass through, while larger particles or impurities are blocked outside. The outer layer of small pore size coating can prevent large particles or impurities from entering the battery, reducing the risk of internal short circuits in the battery. At the same time, this structure also disperses the heat generated during the operation of the battery, improving the thermal stability of the battery. The gradient pore structure enables the diaphragm to better withstand the stress and deformation during the battery charging and discharging process, reducing the risk of diaphragm damage. At the same time, the inner large-pore coating acts as a "reservoir" for the electrolyte, which can alleviate the fluctuation of the electrolyte during the charging and discharging process, thereby extending the battery life.
[0023] Further experiments were conducted based on Example 5, and the results are shown in Table 2: Table 2 Embodiment 3: Embodiment 2 improves the absorption and storage capacity of the diaphragm for the electrolyte and optimizes the service life by making the pore sizes of the inner and outer ceramic coatings different, so as to further increase the service life and stability of the battery, further improvement is made on the basis of Embodiment 2.
[0024] The polydopamine-like layer also contains cerium oxide, and the specific steps are: A dopamine derivative containing a double bond is added to a TRIS-HCl buffer solution containing cerium oxide, stirred and dissolved, and then the semi-finished product is immersed therein, deoxygenated with nitrogen for 30-60 minutes, and then irradiated with ultraviolet light for 4-6 hours before being taken out; wherein the volume content of cerium oxide is 1-5%, and its particle size is 50-100nm.
[0025] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: The presence of cerium oxide particles increases the contact area and interfacial interaction between the polydopamine-like layer and the inner and outer ceramic coatings. Since cerium oxide has good chemical stability and high surface energy, it can form stronger chemical bonds or physical adsorption with the functional groups in the polydopamine-like layer and the components in the ceramic coating. The addition of cerium oxide particles enhances the adhesion between the polydopamine-like layer and the inner and outer ceramic coatings, reduces the risk of interlayer delamination, and improves the overall stability and durability of the diaphragm. The cerium oxide particles change the surface properties of the polydopamine-like layer, improving its wettability to the electrolyte, allowing the electrolyte to be more evenly distributed on the surface of the diaphragm and penetrate into the inner ceramic coating, thereby improving the utilization rate of the electrolyte; The distribution of cerium oxide particles in the polydopamine-like layer will form some tiny pores or channels, providing additional transmission paths for lithium ions and reducing the resistance of ion transmission. The additional ion transmission channels provided by cerium oxide particles enable rapid conduction of lithium ions in the separator, thereby improving ion conductivity, reducing the internal resistance of the battery, and improving the output power and energy efficiency of the battery. By improving the wettability of the electrolyte, cerium oxide particles enable the diaphragm to absorb and retain more electrolyte, which not only improves the utilization rate of the electrolyte, but also reduces the degradation of battery performance caused by insufficient electrolyte; cerium oxide particles can enhance the mechanical strength of the polydopamine-like layer, enabling it to better withstand the stress and deformation during the battery charging and discharging process. At the same time, this also improves the overall mechanical strength of the diaphragm and reduces the risk of diaphragm damage; Through the above series of positive effects, cerium oxide particles extend the service life of the battery, can bring about a more stable diaphragm structure, higher electrolyte utilization and faster ion conduction speed, which work together to improve the performance and stability of the battery.
[0026] The diaphragm prepared in Example 3 was tested, and the results are shown in Table 3: Table 3 Example
[0027] Example 3 also adds cerium oxide particles through the middle layer to improve the integrity and stability of the diaphragm. In order to further optimize the performance of the diaphragm, further improvements are made on the basis of Example 3.
[0028] The cerium oxide particles are large particles of 100-200 nm or small particles of 50-100 nm; The outer ceramic coating contains large or small particles; The middle polydopamine-like layer contains either large or small granules; The inner ceramic coating contains large or small particles; The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: Different combinations can be selected according to the environment or climate differences in different regions. The large-size particles in the inner layer can provide better structural support and increase the mechanical strength of the diaphragm; the small-size particles can fill the gaps more tightly, improve the density of the diaphragm, and have a large specific surface area, which increases the contact area with the electrolyte and is conducive to the rapid conduction of ions. The large-size particles increase the mechanical strength, and the small-size particles increase the density. In the middle layer, large-size particles balance the structural differences between the inner and outer layers; they play a connecting role in the overall performance of the diaphragm; small-size particles improve the density of the middle layer, reduce the path length of ion conduction, and improve the ion conduction performance of the diaphragm; large-size particles balance the structural differences, and small-size particles improve the ion conduction performance; The large particle size in the outer layer can provide better surface protection to prevent damage to the diaphragm; it has a positive effect on the wear resistance and puncture resistance of the diaphragm; the small particle size increases the active surface area of the outer layer, which is conducive to full contact with the electrolyte and improves the ion conductivity of the diaphragm; large particle size particles provide surface protection, and small particle size particles improve ion conductivity; When the inner ceramic coating has large voids, the particle size of the middle cerium oxide layer will affect the properties of the inner layer. When a small particle size is used, cerium oxide can more easily carry polydopamine into the inner ceramic coating and provide a stronger electrolyte holding capacity. In the presence of an outer ceramic coating, the inner cerium oxide particles can exist in both "bound" and "free" states, thereby optimizing the internal structure of the coating, ensuring effective connection and interaction between the particles, and avoiding performance degradation caused by excessive aggregation of particles. At the same time, the "free" cerium oxide particles can increase the flexibility and impact resistance of the coating. When the middle layer uses a large particle size, it is difficult for the cerium oxide particles to penetrate into the inner ceramic coating, and more of them are embedded in the surface of the inner layer close to the middle layer, which enhances the mechanical strength of the coating and acts as a "skeleton" to support the entire coating, making it stronger. In addition, the presence of large-size particles also reduces the stress concentration phenomenon inside the coating, thereby improving the crack resistance and impact resistance of the coating; the embedded structure of large-size cerium oxide particles on the coating surface optimizes the thermal performance of the coating, provides a better heat conduction path, and enables the coating to work stably in a high-temperature environment. At the same time, it reduces the accumulation of thermal stress inside the coating, thereby improving the thermal stability and service life of the coating; The outer ceramic coating can form a tighter bond with the middle layer when using small particles of cerium oxide. The small particles of cerium oxide can be embedded in the pores or defects of the middle layer, thereby enhancing the bonding force between the middle layer and the outer layer, reducing cracks and defects in the coating, and enhancing the overall performance of the coating. The outer ceramic coating can serve as a "skeleton" support when using large particles of cerium oxide, significantly improving the overall strength of the coating and providing a better heat conduction path, so that the coating can work stably in a high temperature environment and reducing the accumulation of thermal stress and performance degradation of the coating caused by temperature changes. The performance of the diaphragm prepared in Example 4 was tested under the conditions that the ethanol content of the inner ceramic coating solvent was 30%, the ethanol content of the outer ceramic coating solvent was 60%, and the cerium oxide content of the middle layer was 3%. The results are shown in Table 4: Table 4 The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A ceramic-based diaphragm for a lithium battery of a new energy vehicle, characterized in that: It includes a PE base film and a ceramic coating on the surface of the PE base film. The ceramic coating contains two layers, an inner layer and an outer layer. A polydopamine layer is grafted between the two ceramic coating layers. The ceramic coating is made by coating with a ceramic coating. The dopamine layer is composed of a dopamine derivative containing a double bond, specifically methacrylamide dopamine. The PE base film is a 25μm microporous film.
2. A ceramic-based diaphragm for a lithium battery of a new energy vehicle according to claim 1, characterized in that: The ceramic slurry comprises the following components: 40-60 parts of nano ceramic aerogel, 5-10 parts of polyethylene-vinyl alcohol sulfonate lithium, 10-15 parts of polyvinylidene fluoride, 5-10 parts of poly(4-styrene sulfonic acid) lithium salt, 3-8 parts of polymer binder, and 35-45 parts of solvent; the nano ceramic aerogel is a ZrO2-SiO2 composite aerogel, and the ZrO2-SiO2 composite aerogel contains rare earth oxide, and the rare earth oxide is specifically CeO2.
3. A ceramic-based diaphragm for a lithium battery of a new energy vehicle as claimed in claim 2, characterized in that: The polymer binder is polyvinyl alcohol, and the solvent includes water and DMAC in a mass ratio of 1:
10.
4. A ceramic-based diaphragm for a new energy vehicle lithium battery as claimed in claim 2, characterized in that: The preparation method of the ZrO2-SiO2 composite aerogel is specifically as follows: Add zirconium oxynitrate to 10%-60% ethanol aqueous solution and stir evenly to obtain a zirconium source solution, add TEOS to 10%-60% ethanol aqueous solution and stir evenly to obtain a silicon source solution, mix the zirconium source solution and the silicon source solution evenly, add CeO2, stir and react in a 50-70°C water bath for 24-36 hours, then add formamide and continue stirring for 30-60 minutes to obtain a mixed sol, soak the mixed sol in ethanol at 40-50°C for aging for 3-6 days, replace ethanol every 12-24 hours, and finally dry it supercritically and then ball mill it.
5. A ceramic-based diaphragm for a lithium battery of a new energy vehicle as claimed in claim 2, characterized in that: The mass ratio of Ce, Si and Zr is 0.05:1:
1.
6. A ceramic-based diaphragm for a lithium battery of a new energy vehicle as claimed in claim 4, characterized in that: The content of the solvent ethanol aqueous solution used in the preparation of the nano ceramic aerogel contained in the outer ceramic coating and the inner ceramic coating is different.
7. A ceramic-based diaphragm for a lithium battery of a new energy vehicle as claimed in claim 6, characterized in that: The solvent of the zirconium source solution and the silicon source solution in the nano-ceramic aerogel in the outer ceramic coating is a 10-30% ethanol aqueous solution; the solvent of the zirconium source solution and the silicon source solution in the nano-ceramic aerogel in the inner ceramic coating is a 40-60% ethanol aqueous solution.
8. A method for preparing a ceramic-based diaphragm for a lithium battery of a new energy vehicle according to any one of claims 1 to 7, characterized in that: The preparation method is specifically as follows: Nano-ceramic aerogel, polyethylene-vinyl alcohol lithium sulfonate, polyvinylidene fluoride, poly(4-styrene sulfonic acid) lithium salt, and polymer binder are added to a solvent and stirred evenly to obtain a ceramic slurry. The ceramic slurry is coated on the surface of a PE base film and cured to obtain a semi-finished product. A dopamine derivative containing a double bond is added to a TRIS-HCl buffer solution, stirred to dissolve, and the semi-finished product is immersed therein. After deoxygenation with nitrogen for 30-60 minutes, the semi-finished product is taken out after irradiation with ultraviolet light for 4-6 hours, and the ceramic slurry is coated again and cured, and then washed alternately with methanol and water and dried.
9. The method for preparing a ceramic-based diaphragm for a lithium battery of a new energy vehicle according to claim 8, characterized in that: The polydopamine-like layer also contains cerium oxide, and the specific steps are: A dopamine derivative containing a double bond is added to a TRIS-HCl buffer solution containing cerium oxide, and after stirring and dissolving, the semi-finished product is immersed therein, deoxygenated with nitrogen for 30-60 minutes, and then irradiated with ultraviolet light for 4-6 hours before being taken out; wherein the volume content of cerium oxide is 1-5%.
10. The method for preparing a ceramic-based diaphragm for a lithium battery of a new energy vehicle according to claim 9, characterized in that: The cerium oxide particles are selected to be large particles of 100-200nm or small particles of 50-100nm; Different combinations of cerium oxide particles are used for the outer ceramic coating, the middle polydopamine-like layer and the inner ceramic coating.
Citation Information
Patent Citations
Lithium ion battery separator containing poly-dopamine and ceramic coatings
CN103682216A
High-stability lithium ion battery diaphragm, preparation method thereof and lithium ion battery
CN107342387A
Diaphragm for lithium ion battery and preparation method thereof
CN110289381A
Ceramic-based diaphragm for new energy automobile lithium battery and preparation method of ceramic-based diaphragm
CN115473007A
Composite diaphragm, cerium oxide with oxygen vacancy and preparation method and application of cerium oxide
CN118431673A
Cited By
Low-temperature lithium battery diaphragm material containing nano ceramic material
CN120784571A